MODEL PERTUMBUHAN UDANG WINDU (PENAEUS MONODON) PADA PADAT PENEBARAN YANG BERBEDA - Armansya, Armansya; A. Masyahoro, A.Masyahoro; Serdiati, Novalina (AgriSains, 2012)
Research location executed Countryside of Tonggolobibi, District of Sojol South Sub-Province of Donggala, the Province of Center Sulawesi. Research to start April month up to Junai month 2012. The study aimed to examine individual growth and biomass models shrimp (Penaeus monodon) at different stocking solid and determining the maximum biomass production and harvesting time is right. Test organism used was Tiger Shrimp (Penaeus monodon) obtained from Hatchery Mamboro Palu, Central Sulawesi province. Then digdaya research ponds at the site until the age of 1 month. The study design used was completely randomized design (CRD), which consists of three treatments with 6 replications to obtain 18 units of experimental plots waring as the treatment of A (solid tail/m2 stocking as many as 10), B (solid stocking as many as 15 tail/m2) and C (solid stocking by 20 tail/m2). The results showed a growth model simulated biomass on treatment B with dense stocking of 15 tail/m2 a solid stocking the best for farming black tiger shrimp cultivation for 4 month period with the total biomass was 1170.3 g. As for the growth model based on the weight and length of the three treatments showed sigmoid curves asymptote. Key words: Model of growth, stocking solid, tiger shrimp.